Venturing from Emerging Economies - Yamakawa, Yasuhiro; Khavul, Susanna; Peng, Mike W.; Deeds, David L. (Strategic Entrepreneurship Journal, 2013)
What drives new ventures to internationalize from emerging economies to developed economies? To answer this underexplored question, we bring together theory at the intersection of international entrepreneurship and strategy in emerging economies. Focusing on intangible resources, we theorize that international expansion of new ventures from emerging economies is driven by their desire to enhance domestic reputation, to exploit their stocks of prior knowledge, and to explore benefits of incoming knowledge flows. We find support for our hypotheses using a cross‐country sample of new ventures from two major emerging economies— C hina and I ndia. Copyright © 2013 Strategic Management Society.